Bioaugmentation treatment of polycyclic aromatic hydrocarbon-polluted soil in a slurry bioreactor with a bacterial consortium and hydroxypropyl-β-cyclodextrin. Issue 21 (19th September 2022) - Guo, Guang; Liu, Chong; Tian, Fang; Ding, Keqiang; Wang, Huiya; Zhang, Can; Yang, Feng; Xu, Jin
ABSTRACT: The aim of the study was to verify the effect of bioaugmentation by the bacterial consortium YS with hydroxypropyl-β-cyclodextrin (HPCD) in a soil slurry. The bacterial consortium YS was enriched from a petroleum-polluted soil using pyrene as sole carbon resource. After 3 weeks, the degradation rate of phenanthrene in CK increased from 22.58% to 55.23 and 78.21% in bioaugmentation (B) and HPCD + bioaugmentation (MB) respectively. The degradation rate of pyrene in CK increased from 17.33% to 51.10% and 60.32% in B and MB respectively in the slurry. The augmented YS persisted in the slurry as monitored by 16S rRNA gene high-throughput sequencing and outcompeted some indigenous bacteria. Enhanced polycyclic aromatic hydrocarbon (PAH) degradation was observed in the addition of HPCD due to the enhanced bioavailability of phenanthrene and pyrene. Additionally, the amount of PAH-degrading bacteria and enzymatic activity in bioaugmentation with HPCD were higher than that in the CK group. The results indicated that bioaugmentation with a bacterial consortium and HPCD is an environmentally friendly method for the bioremediation of PAH-polluted soil. GRAPHICAL ABSTRACT: UF0001